An unusual case report of porokeratosis ptychotropica on the buttocks. Issue 47 (25th November 2022) - Xiao, Yu; Peng, Shanshan; Mao, Tianyi; Li, Xiangjun; Ye, Wenzheng; Fang, Muping
Abstract : Rationale: Porokeratosis ptychotropica represents an unusual form of porokeratosis characterized by symmetrical dyskeratotic skin lesions on the gluteal clefts. Herein, we report a case of porokeratosis ptychotropica. Patient concerns: A 33-year-old man, who complained of itching papules and plaques in the gluteal cleft and the buttocks for the last 7 years. Clinical examination showed a large well-defined reddish brown verrucous plaque located on both buttocks along with satellite papules on the inner thigh. Dermoscopy and histopathological findings were consistent with porokeratosis. Diagnosis: He was diagnosed with porokeratosis ptychotropica. Outcomes: No significant improvement was observed following treatment with oral acitretin and a topical retinoid. Lessons: The case report highlights the need for awareness amongst dermatologists for porokeratosis ptychotropica as a differential diagnosis for pruritic papules in the gluteal fold.